Laboratory Investigations Reveal that Harmonia axyridis (Coleoptera: Coccinellidae) Is a Poor Host for Dinocampus coccinellae (Hymenoptera: Braconidae) in Brazil. Issue 1 (20th June 2016) - de Castro-Guedes, CamilaFediuk; de Almeida, LúciaMassutti
Abstract: Harmonia axyridis (Pallas, 1773) is an Asian coccinellid released in several places to act as a biological control agent of aphids. Dinocampus coccinellae (Schrank, 1802) is an endoparasite that uses more than 40 coccinellid species as hosts. Thus, the aim of this study was to investigate the interactions between D. coccinellae and H. axyridis and to determine the impact of the parasitoid on the establishment capacity of H. axyridis . It was also investigate the influence of host on the development of D. coccinellae using other Coccinellidae species as hosts: Cycloneda sanguinea, (L., 1763) Cycloneda pulchella (Klug, 1829), Eriopis connexa (Germar, 1824), and Olla v-nigrum (Mulsant, 1866) . In no-choice tests, pupa was the least attacked stage, and the fourth instar and adults the most attacked. In choice tests, the pupa was less attacked when combined with all the other stages, and the fourth instar and adults the most attacked. There was statistical difference only for fecundity, fertility, and number of eggs/day, with higher values found in the non-parasitized control group. Due to the low rate of parasitism it is believed that D. coccinellae has little impact on the populations of this coccinellid in Brazil. However, it is noteworthy that an increase in H. axyridis coverage areas can affect the populations of D. coccinellae, as in some places of occurrence, H. axyridis has become the predominant species of Coccinellidae. The result can be a decrease in populations of this species of parasitoid or its better adaptation to the new host.